2016
DOI: 10.1002/art.39553
|View full text |Cite
|
Sign up to set email alerts
|

A Novel HLA–DRB1*10:01–Restricted T Cell Epitope From Citrullinated Type II Collagen Relevant to Rheumatoid Arthritis

Abstract: Objective Antibodies against citrullinated type II collagen (Cit‐CII) are common in the sera and synovial fluid of patients with rheumatoid arthritis (RA); however, the known T cell epitope of CII is not dependent on citrullination. The aim of this study was to identify and functionally characterize the Cit‐CII–restricted T cell epitopes that are relevant to RA. Methods Peripheral blood mononuclear cells (PBMCs) from HLA–DRB1*10:01–positive patients with RA and healthy donors were stimulated in vitro with cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 54 publications
1
28
1
Order By: Relevance
“…Indeed, an example of a peptide that appears negative in MHC binding assays, but still provides functional T cell responses, has been previously identified (22). We therefore assessed the direct binding of biotinylated versions of all the native and citrullinated peptides that did not or did only very weakly displace reference peptides in our competition assays, to plate-bound HLA-DRB1*04:01, *04:04, and *01:01 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an example of a peptide that appears negative in MHC binding assays, but still provides functional T cell responses, has been previously identified (22). We therefore assessed the direct binding of biotinylated versions of all the native and citrullinated peptides that did not or did only very weakly displace reference peptides in our competition assays, to plate-bound HLA-DRB1*04:01, *04:04, and *01:01 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Epitopes were incubated in increasing concentrations in the presence of plate-bound HLA-DRB1*01, *04:01, or *04:04 and 0.02 μM of the biotinylated competitor epitopes HA 306–318 (PKYVKQNTLKLAT) for HLA-DRB1*04:01 and *01:01, and GAD65 270–285 (LPRLIAFTSEHSHFS) for HLA-DRB1*04:04 (21). Finally, peptide-binding affinity to the three different HLA alleles was assessed in direct binding assays in which N -terminally biotinylated epitopes (GenScript, Piscataway, NJ, USA) were incubated at concentrations from 5 to 0.05 μM with plate-bound relevant HLA-DRB1 molecules in the absence of a competitor peptide (22). The inflection point of the binding curve of a known binding epitope was used as a cutoff to separate weakly binding epitopes from background.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has also been shown that citrullination, depending upon the position it is located, could create a new HLA-DR-restricted functional T cell epitope. In this respect, Chemin et al have shown that the HLA-DRB1*10:01-restricted citrullinated-CII 311–325 epitope is a neo T cell epitope where citrulline is in position P2, where it would affect T cell recognition [62]; Gerstner et al [59] have also made similar observations in the context of an alpha-enolase T cell epitope restricted by DRB1*04:01. Thus, the second potential effect of converting arginine to citrulline in a peptide is that it generates a novel TCR interaction site on the peptide when it is bound and presented by the SE+ HLA-DR molecule.…”
Section: Discussionmentioning
confidence: 96%
“…The increased likelihood of ACPAs in RA patients with shared epitope haplotypes and the propensity for these HLA‐DR proteins to present citrullinated peptides suggests that CD4 + T‐cell responses to such epitopes actively contribute to disease. Indeed various studies have identified citrullinated vimentin, aggrecan, α ‐enolase, and collagen peptides that elicit functional T‐cell responses in RA patients. Recognition of these citrullinated proteins by T cells has also been documented in HLA transgenic mice .…”
Section: Recognition Of Citrullinated Epitopes In Ramentioning
confidence: 99%